Psychometric properties and cross-cultural adaptation of the UCLA loneliness scale, 6-item among older Iranian people - Farzaneh Bahadori; Abdolrahim Asadollahi; Ogholgol Ghajari; Mahsa Yarelahi (BMC Psychology)
Abstract Background Loneliness is common in old individuals, and the UCLA loneliness scale is one of the most reliable tools for measuring loneliness worldwide. The present study aimed to investigate the psychometric properties of the 6-item UCLA loneliness scale in the Iranian older population. Methods In this psychometric study, we outline the translation and validation of the 6-item UCLA loneliness scale among 612 older adults with a mean age of 68.2 ± 7.2 years (females = 60.9%) in 2023. The participants were selected via stratified random sampling. Data were collected through face‒to-face interviews via the UCLA Loneliness Scale, Loneliness Scale, Oxford Happiness Scale, and demographic questionnaire. The data were analyzed via SPSS version 26 and AMOS version 25 software. The content validity, construct validity, and internal consistency were investigated, and ROC analysis and convergent validity were also assessed. Results Approximately two-thirds of the participants were married, and three-fourths had at least one chronic condition. The EFA assigned a two-factor solution for the UCLA loneliness scale, confirmed by CFA (GFI = 0.90, CFI = 0.91, and RMSEA = 0.056). Internal consistency was confirmed by the ICCs, Cronbach’s alphas, and McDonald’s Omega values (a ≥ 0.90). The ROC analysis indicated an exact cutoff value for older adults with and without severe loneliness with high sensitivity and specificity. Conclusion The Persian version of UCLA Loneliness Scale, 6-item presented good psychometric properties and could be used to measure loneliness in community-dwelling older adults.